Experimental and Numerical Analysis of Bubbles Distribution Influence in BubbleDeck Slab under Harmonic Load Effect - Mahdi, A. S.; Mohammed, S. D. (Engineering, Technology & Applied Science Research, 2021)
Reducing a structure’s self-weight is the main goal and a major challenge for most civil constructions, especially in tall buildings and earthquake-affected buildings. One of the most adopted techniques to reduce the self-weight of concrete structures is applying voids in certain positions through the structure, just like a voided slab or BubbleDeck slab. This research aims to study, experimentally and theoretically, the structural behavior of BubbleDeck reinforced concrete slabs under the effect of harmonic load. Tow-way BubbleDeck slab of 2500mm×2500m×200mm dimensions and uniformly distributed bubbles of 120mm diameter and 160mm spacing c/c was tested experimentally under the effect of harmonic load. Numerical analysis was also performed with the ABAQUS software. The results of the adopted numerical model were in acceptable agreement with the experimental results. The numerical analysis presented by the bubbles distribution effect was carried out for the BubbleDeck two-way slab under the effect of harmonic load through the evaluated numerical model. Two cases were considered in which the distribution kept the critical positions of the slab free from the bubbles. The results proved that bubbles distribution significantly affected the structural behavior.